Total Factor Productivity Growth and Demographics: The Case of Turkey - Uğur Ursavaş (Ekonomi, Politika & Finans Araştırmaları Dergisi, 2020)
Total factor productivity plays a crucial role in explaining overall economic growth. One of the important factors affecting the total factor productivity is the demographic structure of countries. All countries in the world are likely to experience demographic transition at some point. There are many channels through which demographic transition may impact total factor productivity. If a country wants to take full advantage of the demographic transition, proper policies should be implemented. This paper attempts to investigate the relationship between demographic factors and the likelihood of total factor productivity growth over the period of 1986-2017 in Turkey. Probit regression is applied to analyze the link between total factor productivity and demographic structure. The results show that an increase in income per capita, urban population, life expectancy at birth, and population density increases the likelihood of total factor productivity growth whereas an increase in capital stock per capita, dependency ratio, young dependency ratio, and fertility rate decreases the probability of total factor productivity growth.